Thiamine-responsive acute pulmonary hypertension – A case series and review from a pediatric ICU - Prudhvi Raju Pericherla V; Raghava Badabagni; Sripal Reddy Cheguru; Madhu Kiran Reddy Devireddy; Mabbul Shaik; Prasanth Kumar Battula; Sohail Zeeshan Shaik (Asian Journal of Medical Sciences, 2023)
Pulmonary hypertension is seen in approximately 10% of infants with respiratory distress admitting to pediatric ICUs. Causes can be idiopathic or secondary to lung parenchymal or vascular diseases. Among various causes of pulmonary arterial hypertension, thiamine deficiency (TD) is one of the reversible causes. TD is still prevalent in selected parts of India. This review outlines five typical patients admitted to KIMS, Amalapuram, with thiamine-responsive acute pulmonary hypertension who responded dramatically to thiamine supplementation. It can cause life-threatening pulmonary hypertension in exclusively breastfeeding infants of mothers who are on a restricted diet predominantly consisting of polished and washed rice which can contribute to infant mortality. Thiamine administration based on clinical suspicion and echo findings leads to remarkable recovery. To tackle this fatal disease, a very high degree of awareness and thiamine supplementation in relevant geographical areas is required.